Upaya Peningkatan Motivasi Belajar Siswa Kelas VII G dengan Pendekatan Permainan Pada Mata Pelajaran PJOK di SMP Negeri 1 Kota Kediri - Budi Rohmad Hidayat; Mokhammad Firdaus; Danang Kanda Riyatmojo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
One effective method to increase physical activity among students is to incorporate Physical Education, Sports and Health (PJOK) into the school curriculum. Considering that secondary school students, usually aged between 12 and 15, have a natural inclination towards games, a game-oriented strategy is particularly appropriate, as children generally prefer to engage in fun activities. Through this approach, students are likely to be more motivated to engage in physical activities that are beneficial to their body fitness and health. This study applied the Classroom Action Research (PTK) method implemented in two cycles, with each cycle consisting of two meetings covering physical fitness materials. Data collection techniques were conducted through observation, documentation, and questionnaires to explore students' opinions regarding the learning process provided by the teacher. The study findings stated that the game-based approach proved to be very effective in increasing the motivation to learn PJOK in class VII G SMPN 1 Kota Kediri. Therefore, in learning PJOK, it is important to create interesting innovations so that students are more interested and active in following the learning.